Antifungal Activity of Methanolic Extract of the Brown Seaweed Turbinaria ornata (Turner) J. Agardh, from Tomini Bay against Candida albicans. (April 2019) - Zubair, M S; Ardiana,; Nugrahani, A W
Abstract: The brown seaweed Turbinaria ornata has been reported to possess diverse biological activities. This study aimed to evaluate the antifungal activity of Turbinaria ornata seaweed collected from Tomini Bay against Candida albicans and determine the compounds that might contribute to the antifungal activity. Turbinaria ornata seaweed extract was obtained by maceration using methanol 96% for 3 × 24 h. The filtrate obtained was then evaporated by rotary evaporator to obtain a viscous extract. Antifungal activity was tested using the agar diffusion method. Antifungal compounds were determined by bioautographic-TLC and identified using TLC reagent spray. The results showed that the methanolic extract of Turbinaria ornata possessed an inhibition zone with a diameter of 22.28 mm ± 0.63. Bioautographic-TLC test with eluent of n-hexane:ethyl acetate (7:3) found that a terpenoid (Rf value 0.71) appeared to contribute to the antifungal activity